RESILIENSI REMAJA YANG PERNAH MENGALAMI KEHAMILAN TIDAK DI INGINKAN AKIBAT HUBUNGAN SEKS SEBELUM MENIKAH: STUDI KUALITATIF - Sejati, Putri Eka; ISTIGHOSAH, NINING -; Laisuwannachart, Panjarut . (Jurnal Medikes (Media Informasi Kesehatan), 2023)
Teenagers who are unmarried and experience unwanted pregnancies get negative effects, namely experiencing psychological stress. The main stress experienced is fear of stigmatization from the environment, negative reactions from partners, parents feel disappointed, and expulsion from school. Teenagers get a lot of negative impacts and experience difficult situations from unwanted pregnancies due to premarital sexual relations and new roles as young mothers so they need to have the ability to adapt and survive when experiencing bad or broken events in their lives which are known as resilience. The method used in this study is qualitative while the focus of the research is to describe the resilience of adolescents who have experienced unwanted pregnancies as a result of premarital sex. The results of this study are that all informants are currently in the process of becoming resilient. The resilience within the three informants comes from three sources, namely I have, I am, and I can resilience. Key word: Premarital sex, Resilience, Unwanted Pregnancy